PENGARUH VARIASI LATIHAN ENDURANCE TRAINING UNTUK MENINGKATKAN VO2MAX PEMAIN SEPAK BOLA KLUB SANHERIB FC - Yoggi Prananda; Victor. G. S; Novi Yanti (Universitas Tanjungpura, 2021)
AbstractThe purpose of this study was to maximize the cardio vascular ability (vo2max) of soccer players, namely to increase the strength of the lungs and heart of the players by providing variations of Endurance Training exercises to Sanherib Fc players. This research uses quantitative descriptive analysis with experimental research methods and this research plan uses a one group pre-test-post-test design and uses a research instrument in the form of a Multistage Fitness Test (MFT). The subjects of this study were all Sanherib Fc players who found 20 people located in Peniti Village, Sekadau Regency. Based on the results of research in the field, there is a very significant effect of variations in Endurance Training on the Vo2max ability of the Sanherib Fc football club players with a very extraordinary increase of 23.52%, from these results it can be concluded that there is an influence on the Vo2max ability of the players. given after treatment or treatment for 9 meeting.Keywords: Soccer, Vo2max, Endurance Training